Effect of Corona Virus Disease (Covid-19) Distribution, Number of Positive People on World Crude Oil Prices - Yusraida Khairani Dalimunthe; Ni Komang Indah Trisanti (Journal of Earth Energy Science, Engineering, and Technology, 2022)
The spread of Coronavirus Disease (COVID-19) in all parts of the world has an impact on various sectors such as the economy, especially the price of world crude oil. This study aims to analyze the influence of the spread of COVID-19 based on the number of positively infected people on world crude oil prices with statistical correlation analysis. The correlation coefficient results in the number -0.726, which means that the variable number of Corona positive people on the world crude oil price variable has a strong and significant relationship. With the increasing number of positive people infected with COVID-19, the world crude oil price actually decreases because the resulting relationship is in the opposite direction through the correlation coefficient, where a very significant decline in world crude oil prices due to the COVID-19 pandemic has affected the global economy.